STUDI KOMPARASI INTERPRETASI QS. LUQMAN: 19 DAN QS. AL-HUJURAT: 2 TENTANG ADAB MENGELOLA INTONASI SUARA DALAM DAKWAH - Putri Anggraini; Komarudin Sassi (CV. Lafadz Jaya, 2026)
This study aims to analyze the concept of voice intonation management in Surah Luqman verse 19 and Surah Al-Hujurat verse 2 and its relevance to contemporary communication and da'wah. The research employs a qualitative approach using library research, thematic interpretation (maudhu’i), and comparative analysis. The findings reveal that Surah Luqman verse 19 teaches the importance of self-control in managing voice intonation to ensure that communication remains polite, effective, and persuasive. Meanwhile, Surah Al-Hujurat verse 2 emphasizes the importance of respecting the audience as the foundation for establishing harmonious and dignified relationships. Comparative analysis shows that these two verses form a Qur’anic communication paradigm based on self-regulation, respect for others, and social responsibility. This concept is relevant to various modern communication theories and serves as an ethical foundation for developing humane, moderate, and civilized communication in the digital era.